2015
DOI: 10.1161/circgenetics.114.000554
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for PLASMINOGEN as a Shared Genetic Risk Factor of Coronary Artery Disease and Periodontitis

Abstract: Background— Genetic studies demonstrated the presence of risk alleles in the genes ANRIL and CAMTA1/VAMP3 that are shared between coronary artery disease (CAD) and periodontitis. We aimed to identify further shared genetic risk factors to better understand conjoint disease mechanisms. Methods and Results— In-depth genotyping of 46 published CAD risk loci o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 45 publications
4
78
0
1
Order By: Relevance
“…Mutation, abnormal expression, and mislocalization of vesicular transport proteins have been observed in various cardiovascular diseases, including atherosclerosis (22,23). However, there is only a limited understanding of the pathophysiology of vesiculartransport-associated cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation, abnormal expression, and mislocalization of vesicular transport proteins have been observed in various cardiovascular diseases, including atherosclerosis (22,23). However, there is only a limited understanding of the pathophysiology of vesiculartransport-associated cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“… Shared genetic risk factors Obviously, there may be unknown shared risk factors of importance, including the genetic profile of patients with the two diseases. For example, a shared variant in the IL-1 gene complex could be part of the background for the simultaneous occurrence of both diseases, and recent studies have identified a number of other shared genetic risk factors [29,30]. However, these factors do not appear to explain the observed association fully.

PDIS, periodontitis; CVD, cardiovascular disease; AMI, acute myocardial infarction.

…”
Section: Explanatory Modelsmentioning
confidence: 99%
“…In the latter study, variants within the IRF5 and PRDM1 genes were suggested to be associated with AgP, but not robustly validated; the proteins encoded by these genes play a role in interferon-beta signaling (76). In a similar fashion, recently new candidate genes for AgP were identified by exploring the well-established risk genes for coronary artery disease (CAD) (75). The CADassociated gene PLG (plasminogen), was significantly associated with AgP in both an explorative cohort and a validation cohort.…”
Section: Glt6d1 On Chromosomementioning
confidence: 99%